THE SIGNIFICANCE OF WAQF FOR ECONOMIC DEVELOPMENT - Budiman, Mochammad Arif (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
Terdapat anggapan dari sejumlah ilmuan Barat yang menyatakan bahwa institusi wakaf tidak lagi memainkan fungsi ekonomi yang signifikan dalam konteks perekonomian modern sebagaimana pada masa-masa sebelumnya. Menurut mereka, wakaf pada masa kini justru muncul sebagai faktor yang menghambat pembangunan di negara-negara Muslim. Artikel ini dimaksudkan untuk membantah anggapan tersebut dengan menampilkan berbagai fungsi dan kontribusi ekonomi yang dapat diperankan wakaf dalam konteks perekonomian kontemporer. Selain itu, sejumlah prasyarat untuk lebih mengoptimalkan pengelolaan wakaf juga dikemukakan.Kata kunci: wakaf, pembangunan ekonomi, distribusi pendapatan, kemiskinan, pembiayaan defisitThere is an opinion among Western scholars that the institution of waqf could not any longer perform its economic role in the present times. Instead of being a vital institution as it truly played at the pre-modern era, waqf nowadays seems to be an impediment to the development in Muslim countries. This paper therefore is meant to refute such an opinion and attempts to point out the economic impacts of waqf for Muslim society in the context of the present economy. In the last part, the paper also brings about several necessary prerequisites for the revitalization of waqf in the current days.Keywords: waqf, economic development, income distribution, poverty, deficit financing